Determinants of Financial Decisions of Millennial Generation in Islamic Banking: Does Islamic Branding Matter? - Abid Djazuli; Muhammad Ridhwan Ab Aziz; Mister Candera; Darma Yanti (Journal of Accounting and Investment, 2023)
Research aims: This study aims to determine the financial decisions of the millennial generation by considering the Islamic financial literacy variables, reflected by the financial behavioral, knowledge, and attitude variables, and Islamic branding as a mediating variable.Design/Methodology/Approach: The approach used in this study was empirical. Utilizing questionnaires distributed through various online media, the data were collected. The research samples included the millennial generation in South Sumatra, filtered using a purposive sampling technique. To evaluate the hypotheses, Structural Equation Modeling (SEM) was employed. Research findings: The study findings highlighted that Islamic financial literacy directly had a positive and significant impact on the financial decisions of the millennial generation in South Sumatra. Islamic branding could also mediate (partial mediation) the influence of Islamic financial literacy on financial decisions. Theoretical contribution/Originality: This finding can be used as a reference for companies to increase the number of customers and investors, especially among the millennial generation. Specifically, Islamic branding can be recommended as one of the sharia banking business strategies to improve the financial decisions of the millennial generation.Research limitation/Implication: This study was only conducted in South Sumatra, making the result not quite strong in terms of external validity.